Shared Sovereignty, Limited Equality: The Tension Between Member States and Supranationalism - Safta, Marieta; Toader, Tudorel (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The Chapter investigates the evolving concept of sovereignty within the EU, highlighting the balance between national autonomy and European integration. Thus, Member States have transferred aspects of their sovereign powers to EU institutions, creating a governance framework that is polycentric and non-hierarchical. This model allows for collective decision-making, enhancing the EU’s global influence, but it also generates tensions and questions concerning the undermining of national sovereignty and inequalities in decision-making processes. Additionally, disputes over the supremacy of EU law versus the supremacy of national constitutions and constitutional identity highlight persistent challenges in the integration process. The study explores the constitutional aspects of sovereignty within the EU, focusing on the principle of conferred competencies and the relationship between national and supranational governance. It examines the evolution of the EU as an autonomous legal order, specifically addressing areas such as fundamental rights protection and criminal law, which have traditionally been associated with national sovereignty. The analysis weighs up how various crises, such as those related to the rule of law, and contemporary challenges like cybersecurity and artificial intelligence highlight the necessity for supranational solutions. It also examines whether the strengthening of supranational authority undermines state sovereignty or contributes to a more cohesive and resilient Union. The main conclusion is that the concept of ‘shared and responsible sovereignty’ better describes balanced development and provides a solid framework for the future evolution of the EU.